Aesthetics configuration in the Assyrian winged bull )An analytical study( (Al-Academy, 2017)
Subjected Find winged bull Assyrian monetary analysis in order to identify the formative relations in terms of percentages, movement and public swab for being aesthetic values ​​upon which the mechanisms of artistic composition, which did not give researchers artistic interest that affects the status of these sculptures and the like of the achievements of the Iraqi civilization in Assyria.Resulting analysis to a number of the most important results, the percentages approved in the calculation of the parts to do with all when viewed status horizontal with a realistic formulas while in the case of considering frontally clear for Ras stylized proportions and head size larger in length, a ratio confirmed by previous studies, and that the kinetic relations dynamic came overlapping format shows leapfrog the wing and speed in the legs and feet of the camel that mimic the movement in terms of exchange relations, and finally recommended the search three substantive recommendations